2017
DOI: 10.1007/s10803-017-3142-0
|View full text |Cite
|
Sign up to set email alerts
|

Verbal, Visual, and Intermediary Support for Child Witnesses with Autism During Investigative Interviews

Abstract: Three promising investigative interview interventions were assessed in 270 children (age 6–11 years): 71 with autism spectrum disorder (ASD) and 199 who were typically developing (TD). Children received ‘Verbal Labels’, ‘Sketch Reinstatement of Context’ or ‘Registered Intermediary’ interviews designed to improve interview performance without decreasing accuracy. Children with ASD showed no increases in the number of correct details recalled for any of the three interview types (compared to a Best-Practice poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 44 publications
(76 reference statements)
2
40
0
Order By: Relevance
“…However, the findings also emphasise that children on the autism spectrum may need more support (e.g. more open-ended prompts or possibly more comprehensive investigative interviews, see Henry et al, 2017) to provide their best evidence.…”
Section: Discussionmentioning
confidence: 89%
“…However, the findings also emphasise that children on the autism spectrum may need more support (e.g. more open-ended prompts or possibly more comprehensive investigative interviews, see Henry et al, 2017) to provide their best evidence.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies, researchers have assessed children's or adult's memories twice, using delays that ranged from immediately and a few hours or days after the event (Gaigg & Bowler, ; Henry, Crane, et al, ; Maras et al, ; North, Russell, & Gudjonsson, ) to 8 and 12 days after the event (Bruck, London, Landa, & Goodman, ). These studies, however, have not examined changes in the amount and accuracy of information autistic children reported about the experienced or witnessed events in the two interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Most eyewitness studies suggests that, after short delays, children and adults with ASD tend to recall less information than TD peers (Bruck et al, ; Henry, Messer, et al, ; Mattison et al, ; Mattison, Dando, & Ormerod, ; McCrory et al, ; Millward et al, ). However, various studies have also reported that autistic individuals can provide as much correct information about an event as TD peers, especially when appropriate support is given at retrieval (Henry, Crane, et al, ; Maras et al, ; Maras & Bowler, ). With regard to the accuracy of the information recalled soon after an event, the research findings are also not consistent, with some suggesting that individuals with ASD are less accurate than non‐ASD peers (e.g., Bruck et al, ; Maras & Bowler, , , ), whereas others have found that they are just as accurate (e.g., Henry, Crane, et al, ; Henry, Messer, et al, ; Maras et al, ; Maras et al, ; Maras & Bowler, ; McCrory et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations